Pelatihan dan Pendampingan E-Learning Berbasis Edmodo untuk Meningkatkan Kompetensi Profesional Guru Era Revolusi Industri 4.0 - Lutfiana, Rose Fitria; Mansur, M. (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
This community service activity aims to provide training and mentoring to teachers in SMP Muhammadiyah 1 Malang related to edmodo-based e-learning. After participating in training and mentoring activities, teachers are expected to be able to master edmodo-based e-learning. Community service activities carried out in SMP Muhammadiyah 1 Malang City which addressed Jl. Brigadier Slamet Riadi No.134, Oro-oro Dowo, Kec. Klojen, Malang City, East Java 65119. The method of implementing the activity consisted of focus group discussions, training and mentoring. The result of this community service activity is to improve the professional competence of teachers in the industrial revolution era 4.0.